PERAN FASILITATOR DALAM PEMBERDAYAAN KELOMPOK TANI PESERTA PROGRAM READSI DI DESA TRIMULYA KECAMATAN ONEMBUTE KABUPATEN KOLAKA TIMUR - Gion Junaidi; Dasmin Sidu; Putu Arimbawa (Universitas Halu Oleo, 2022)
The objective of this investigation is to examine the facilitator's function in enhancing the participation of farmer groups in the READSI program and to establish the correlation between the facilitator's role and the empowerment of farmer groups involved in the READSI program. The study was conducted in March 2022. The population of the investigation consisted of all members of the farmer group involved in the READSI program. The sample size was determined using the Proportional Random Sampling technique, and it included 45 individuals. The analysis of the data was performed using descriptive statistics and Spearman Rank Correlation analysis. The findings indicated that the facilitator's role in Trimulya Village, Onembute District, Konawe Regency, was of excellent quality. The farmer groups' empowerment was demonstrated by their capacity to handle the received information, make decisions concerning their farming, manage farming activities, market their farming products, and apply agricultural innovation technologies. There is a significant correlation between the facilitator's role and the empowerment of farmer groups.